Thermal and dynamic-mechanical properties of silane functionalized graphene oxide (GO)/Epoxy nanocomposites coatings - Aujara, Kabiru M.; Ibrahim, Nor A.; Zainuddin, Norhazlin; M. Nor, Siti M.; Ratnam, Chantara T. (Research and Technology Transfer Affairs Division,Khon Kaen University, 2023)
In this study, graphene oxide (GO) and functional-GO (f-GO) were incorporated into epoxy (EP) resins to provide a protective layer for the metal substrate. Functional-GO is synthesized using environmentally friendly gamma irradiation techniques by incorporating methyltriethoxysilane (MTES) to its surface by radiation from gammaray. GO, and functionalized-GO are characterized via fourier transform infrared spectroscopy (FTIR), x-ray diffractometer (XRD), and thermogravimetric analysis (TGA). Evidence of silane grafting is indicated by the presence of new peaks in the FTIR spectra of the functionalized GO. The crystal surface changes and surface defects due to modification are determined by XRD. The TGA thermograms showed an increase in weight loss due to the grafting of silane in the 300-650°C associated with the chemically bonded silane degradation on the GO from 0 to 32.17 for GO and TGO-150 respectively. Preparation of the steel substrate protective material begins by ultrasonically dispersing the GO in the solvent before mixing it into an epoxy matrix and adding a hardener. XRD showed the existence of GO morphology and f-GO intercalation and exfoliation throughout the matrix. TGA and dynamic mechanical analysis (DMA) are employed to investigate nanocomposite coatings’ thermomechanical properties. The TGA thermogram showed a decrease in percentage weight loss at 350°C (W350°C) from 29 for neat epoxy (EP) to 19.8 for ETG-150. Similarly, DMA analysis also showed an increase of Tan δ from 1953.30 MPa to 3414.90 MPa and Tg from 80.18°C to 90.49°C for EP and ETG-150 respectively.